2014
DOI: 10.1016/j.molcel.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

MICU1 and MICU2 Finely Tune the Mitochondrial Ca2+ Uniporter by Exerting Opposite Effects on MCU Activity

Abstract: SummaryMitochondrial calcium accumulation was recently shown to depend on a complex composed of an inner-membrane channel (MCU and MCUb) and regulatory subunits (MICU1, MCUR1, and EMRE). A fundamental property of MCU is low activity at resting cytosolic Ca2+ concentrations, preventing deleterious Ca2+ cycling and organelle overload. Here we demonstrate that these properties are ensured by a regulatory heterodimer composed of two proteins with opposite effects, MICU1 and MICU2, which, both in purified lipid bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
634
2
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(696 citation statements)
references
References 23 publications
46
634
2
14
Order By: Relevance
“…Higher molecular mass (ϳ720 kDa) complexes have also been described, and their existence depends on EMRE and MICU1/2 (3,4,34). Consistently, size exclusion chromatography suggested very large complexes incorporating a major portion of the MCU and EMRE pool to be on a par with the blue dextran (2 MDa).…”
Section: Discussionmentioning
confidence: 84%
“…Higher molecular mass (ϳ720 kDa) complexes have also been described, and their existence depends on EMRE and MICU1/2 (3,4,34). Consistently, size exclusion chromatography suggested very large complexes incorporating a major portion of the MCU and EMRE pool to be on a par with the blue dextran (2 MDa).…”
Section: Discussionmentioning
confidence: 84%
“…MICU2 is a negative MCU modulator as it forms the MICU1/ MICU2 heterodimer, thus sequestering MICU1 and preventing the MICU1 homodimer stimulatory activity on MCU, as we recently demonstrated. 19 Indeed, we detected the presence of MICU1 homodimers in control but not in Pat#1 fibroblasts (Supplementary Figure S3h). Such an imbalance of MCU regulators could explain the reduced efficiency of mitochondrial Ca 2+ uptake in 13514A4G cells.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we recently reported that MICU1 homodimer and MICU1/MICU2 heterodimer regulates MCU sensitivity to extramitochondrial [Ca 2+ ] and exert opposite effects on the activity of the channel (stimulatory for MICU1 and inhibitory for MICU2). 19 The analysis of the ratio between MICU1/MICU1 and MICU1/MICU2 dimers in nonreducing conditions showed that two bands were present in control fibroblasts, corresponding to the MICU1/MICU2 heterodimer and the MICU1 homodimer. Conversely, Pat#1 cells lacked the MICU1 homodimer (Supplementary Figure S3h), which is responsible for the rapid and efficient mitochondrial Ca 2+ uptake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent identification of several protein families making up the mitochondrial Ca 2+ uniporter complex (MCUC) in mammals, including the pore-forming MCU (MCU and MCUb;Baughman et al, 2011;De Stefani et al, 2011;Raffaello et al, 2013), and the regulatory, associated MICUs (MICU1, 2, and 3; Perocchi et al, 2010;Plovanich et al, 2013), EMRE (Sancak et al, 2013), and MCUR1/CCDC90A (although potentially not directly; Mallilankaraman et al, 2012b;Paupe et al, 2015), has spurred intense research across the biomedical disciplines Mallilankaraman et al, 2012a;Csordás et al, 2013;Hoffman et al, 2013;Marchi et al, 2013;Pan et al, 2013;Raffaello et al, 2013;Kovács-Bogdán et al, 2014;Logan et al, 2014;Patron et al, 2014;Wang et al, 2014). While some genes of the complex components appear not to be present in plants (e.g., MCUb and EMRE), others have multiple homologs (six for the functional poreforming subunit MCU in Arabidopsis [Stael et al, 2012] and maize [Zea mays; Meng et al, 2015] and two for MCUR1/CCDC90A in Arabidopsis), suggesting potential functional modification and/or differentiation.…”
Section: Introductionmentioning
confidence: 99%